(untitled) (Global Journal of Computer Science and Technology, 2013)
Data mining provides tools to convert a large amount of knowledge data which is user relevant. But this process could return individual2019;s sensitive information compromising their privacy rights. So, based on different approaches, many privacy protection mechanism incorporated data mining techniques were developed. A widely used micro data protection concept is k-anonymity, proposed to capture the protection of a micro data table regarding re-identification of respondents which the data refers to. In this paper, the effect of the anonymization due to k-anonymity on the data mining classifiers is investigated. NaEF;ve Bayes classifier is used for evaluating the anonymized and non-anonymized data.